Clinical Features and Management of Status Epilepticus in the Pediatric Intensive Care Unit. Issue 3 (16th March 2023) - Soydan, Ekin; Guzin, Yigithan; Topal, Sevgi; Atakul, Gulhan; Colak, Mustafa; Seven, Pinar; Sandal, Ozlem Sarac; Ceylan, Gokhan; Unalp, Aycan; Agin, Hasan
Abstract : Objectives: Status epilepticus (SE) is associated with significant morbidity and mortality in children. SE in the pediatric intensive care unit (PICU) are not well characterized. The aim of this study is to retrospectively investigate the clinical features and treatment of seizures in children admitted to the PICU of our hospital. Methods: We retrospectively examined the clinical characteristics of patients aged between 1 month and 18 years who were admitted to our hospital with SE or who were diagnosed with SE after hospitalization and were followed up with continuous electroencephalographic monitoring between January 2015 and December 2019 Results: A total of 88 patients with SE, 50 (56.8%) boys and 38 (43.2%) girls, were included. The median age was 24 months (interquartile range, 12–80 months). When we evaluate the continuous electroencephalographic monitoring data, 27 (30.7%) were lateralized, 20 (22.7%) were multifocal, 30 (34.1%) were generalized, and 11 (12.5%) were bilateral independent epileptic activity. Seventy nine patients (89.8%) were evaluated as convulsive status epilepticus (CSE) and 9 (10.2%) as nonconvulsive status epilepticus (NCSE). Pediatric Risk of Mortality (PRISM III) score and mortality of patients with NCSE were higher ( P = 0.004 and P = 0.046, respectively). Thirteen eight patients (43.1%) were diagnosed as SE, 38 patients (43.1%) as refractory SE, and 12 patients (13.6%) as super-refractory SE. The overall mortality rate was 10.2%. Conclusions: Status epilepticus is a neurological emergency that causes mortality and morbidity. Electroencephalographic monitoring is important for the recognition of seizures and rapid intervention. No superiority of second-line treatments or combined treatments was demonstrated in patients with SE.